Vibrational Spectral and Analysis of cis-Decahydronaphthalene - Mani, P.; Suresh, S. (Asian Journal of Chemistry, 2011)
FTIR and FTR spectra of cis-decahydronaphthalene have been recorded in the regions 4000- 200 and 4000-30 cm-1. The vibrational analysis has carried out by assuming Cs symmetry. The observed frequencies were assigned to various modes of vibrations on the basis of intensity, frequencies from allied molecules and the normal coordinate calculations. The potential energy distributions associated with normal modes are also reported here. The assignment of fundamental vibrational frequencies for cis-decahydronaphthalene agrees with the calculated frequencies.